2012
DOI: 10.3184/095422912x13338055043100
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution and physiological changes in the leaves of some shrub, palm and tree species in urban areas of Adana, Turkey

Abstract: The effects of anthropogenic pollution on metal accumulation and some physiological parameters were investigated in plant leaves in the Adana, located in the Mediterranean region of Turkey. Washingtonia filifera L., Eucalyptus camaldulensis L., Phoenix dactylifera L., Platanus orientalis L., Citrus aurantium L., Nerium oleander L. and Schinus molle L. plants were collected from four different locations having different pollution levels in Adana . Concentrations of metals (Al, B, Ba, Fe, Pb, Sr and Zn), pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
(59 reference statements)
4
16
0
4
Order By: Relevance
“…Nevertheless, the species is widely used for medicinal purposes. The findings of the present study are consistent with several previous reports that eucalyptus species accumulate some PTEs in leaves 7,22,23. Children who consume these TMRs may be at higher risk than adults, especially in the winter season when the common cold and flu occur more frequently.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, the species is widely used for medicinal purposes. The findings of the present study are consistent with several previous reports that eucalyptus species accumulate some PTEs in leaves 7,22,23. Children who consume these TMRs may be at higher risk than adults, especially in the winter season when the common cold and flu occur more frequently.…”
Section: Discussionsupporting
confidence: 92%
“…reported higher concentrations for Cu, Pb and Zn in E. camaldulensis sampled from urban parks and streets of Adana city in Turkey 22. Variations in concentrations could be explained by the total PTE in the tailings, leaves and tailings characteristics such as pH and OM, which influence their bioavailability.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that Cu deficiency and excess influence many enzymes that catalyze oxidation and reduction reactions [50,51]. Depending upon the tree species the suitable Cu concentrations for trees range from 2 to 20 ppm and the phytotoxic level is nearly 30 ppm [55]. The current finding of Cu in leaf tissues of both the species was in the line of the prior discussed works of various researchers.…”
Section: Proline and Copper Accumulation In Response To Urban Air Polsupporting
confidence: 72%
“…In recent years, many studies have been carried out in Turkey to study the possible use of various tree species as a possible biomonitor for metals [11][12][13][14][15][16][17][18][19]. However, only limited numbers of studies have been conducted in Istanbul in the last decade [20][21][22].…”
Section: Introductionmentioning
confidence: 99%